SISTEM SAPAAN BAHASA MELAYU RIAU SUBDIALEK INUMAN KABUPATEN KUANTAN SINGINGI - Faizah, Hasnah Faizah Hasnah; ', Lisniarti; ', Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study aims to describe the System Greeting Sub-dialect Inuman Riau Malay Language. The greeting system that kinship and non-kinship greeting. In addition, the study also discusses the changes of address and the factors that cause these changes. This research is a descriptive qualitative research. The results of the research is a classification system of kinship and non-kinship address, change of address, as well as the causes of these changes. The result of this research is a form of greeting documentation contained in Inuman community in Kunatan Singingi. Keys words: system greeting, change of address.